Enzymatic Bioweathering and Metal Mobilization From Black Slate by the Basidiomycete Schizophyllum commune - Kirtzel, Julia; Madhavan, Soumya; Wielsch, Natalie; Blinne, Alexander; Hupfer, Yvonne; Linde, Jörg; Krause, Katrin; Svatoš, Aleš; Kothe, Erika (Frontiers in Microbiology, 2018)
Schizophyllum commune is a filamentous basidiomycete causing white-rot in many wood species with the help of a broad range of enzymes including multicopper oxidases such as laccases and laccase-like oxidases. Since these enzymes exhibit a broad substrate range, their ability to oxidatively degrade black slate was investigated. Both haploid monokaryotic, and mated dikaryotic strains were able to grow on black slate rich in organic carbon as sole carbon source. On defined media, only the monokaryon showed growth promotion by addition of slate. At the same time, metals were released from the slate and, after reaching a threshold concentration, inhibited further growth of the fungus. The proteome during decomposition of the black slate showed induction of proteins potentially involved in rock degradation and stress resistance, and the gene for laccase-like oxidase mco2 was up-regulated. Specifically in the dikaryon, the laccase gene lcc1 was induced, while lcc2 as well as mco1, mco3, and mco4 expression levels remained similar. Spectrophotometric analysis revealed that both life forms were able to degrade the rock and produce smaller particles.